2016
DOI: 10.1155/2016/3271579
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation Induced by Surgery Does Not Impair the Reference Memory of Young Adult Mice

Abstract: Postoperative cognitive dysfunction (POCD) increases morbidity and mortality after surgery. But the underlying mechanism is not clear yet. While age is now accepted as the top one risk factor for POCD, results from studies investigating postoperative cognitive functions in adults have been controversial, and data about the very young adult individuals are lacking. The present study investigated the spatial reference memory, IL-1β, IL-6, and microglia activation changes in the hippocampus in 2-month-old mice af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Its decrease was shown to affect BFCN functions, resulting in memory issues in Alzheimer's disease 38 . Impaired NGF signaling pathway is also described in mild cognitive impairment resulting to aging 38 or sepsis 23 , and recent therapeutic approaches in secondary cognitive impairments are aiming to restore normal expression or/and level of NGF 49 . We hypothesize that the decrease in brain NGF levels observed in FI mice 28 days after surgery, more than a marker of memory dysfunction, plays an active role in the processes leading to cognitive impairment after surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its decrease was shown to affect BFCN functions, resulting in memory issues in Alzheimer's disease 38 . Impaired NGF signaling pathway is also described in mild cognitive impairment resulting to aging 38 or sepsis 23 , and recent therapeutic approaches in secondary cognitive impairments are aiming to restore normal expression or/and level of NGF 49 . We hypothesize that the decrease in brain NGF levels observed in FI mice 28 days after surgery, more than a marker of memory dysfunction, plays an active role in the processes leading to cognitive impairment after surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental research, murine tibial fracture is one of the most widely used animal model to mimic POCD 15,21,22 . It combines sufficient tissue destruction and chronic pain to allow neurologic impairments even in young adult mice, while other models of surgery-induced cognitive decline -such as splenectomy 23 and laparotomy 24,25 -need to be executed in more susceptible mice (older or females). However the longer period of its histological and functional recovery (>4 weeks 26 ) can limit the proper highlighting of POCD during the first month after surgery, as most of murine behavioral assessments require spontaneous locomotion without any sensitivity or mechanical bias.…”
mentioning
confidence: 99%
“…Before the MWM test, mice were individually handled for 2 min each day for 1 week. As described previously (Zhao et al., ), four training days were allowed for the reference memory test. The platform was located in the center of the fourth quadrant.…”
Section: Methodsmentioning
confidence: 99%
“…However, the results of basic studies are varied. Our previous study demonstrated that anesthesia/surgery had no effects on the reference memory of adult mice measured by the Morris Water Maze (MWM)(Zhao et al., ). Other studies obtained similar results (Feng et al., ; Wan et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The neural system of aged individuals is more susceptible than that of young adults [24,25]. Our previous study showed that a single surgery (splenectomy) did not impair the spatial reference memory of young adult mice in spite of the increased IL-1β/IL-6 and activated microglia [26]. The powerful immune system may be helpful in reducing and resolving neuroinflammation after anesthesia/surgery.…”
Section: Discussionmentioning
confidence: 99%